Modelling of Human Cerebral Blood Vessels for Improved Surgical Training: Image Processing and 3D Printing - Jacinda, Reica Diva; Yossy, Nebrisca Patriana; Menik Dwi Kurniatie; Hawar, Ihtifazhuddin; Setiawan, Andreas Wilson; Adidharma, Peter; Prasetya, Mustaqim; Desem, Muhammad Ibrahim; Asmaria, Talitha (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
Human cerebral blood vessels are highly intricate and significantly contribute to brain function support. In the surgical process of these vessels, the neurosurgeons will basically employ magnetic resonance imaging (MRI) as an imaging media to understand the location of the disorder, the anatomical position of vessels, and a guide in the surgical process. However, the usage of MRI data remains a challenge for surgeons in understanding anatomical structures in greater detail, as well as the limitations of training in handling difficult cases. This study aims to provide further technology, combining three-dimensional (3D) image models and 3D printing to accommodate the lack of visualization and pre-operative simulation using MRI data. First, the MRI data would be exported to a software 3D slicer that has the ability to process images with a threshold method to segment the required body parts and generate 3D models. Then, the 3D model of blood vessels would be imprinted using the SLA method to provide the complex anatomical structures of blood vessels. The results from both 3D image modeling and 3D printing have been validated and have dimensions similar to those of the MRI data, indicating that this work is highly accurate. This work significantly helps the surgeons to have a better plan for the surgery steps, identify potential issues before the procedure begins, and develop more precise approaches.